Folk Religion in Discourse and Practice - James Alexander Kapaló (Journal of Ethnology and Folkloristics)
‘Folk religion’ is a contested category within the study of religions, with scholars increasingly advocating its abandonment. This paper encourages a new critical engagement with ‘folk religion’ as both a category of analysis and as a field of practice. I argue for a renewed attentiveness to the ideological dimensions of categories deployed by scholars and to the relationship they bear to the field of practice they seek to signify. Firstly, I explore the discursive nature of the construction of ‘folk religion’ as a category of analysis and how its semantic loading functions to ‘pick up’ distinctive practices from the religious field. Secondly, drawing on the work of Bourdieu and Riesebrodt, I characterise the ‘folk religious field of practice’ as relational, a shifting site of competing agencies. My argument is illustrated with empirical examples drawn from ethnographic research in Romania and Moldova.